Strategi Keberlanjutan Usahatani Mina Padi di Kalurahan Candibinangun Kapanewon Pakem Kabupaten Sleman - Nadia, Zahrima; Ina Fitrian Ismarlin; RR. Siti Astuti (Rawa Sains: Jurnal Sains STIPER Amuntai, 2025)
Mina padi is a rice-fish farming an agricultural innovation that integrates rice and fish cultivation on a single plot of land with the aim of increasing land productivity and water resource efficiency. Mina padi is a form of agricultural innovation that prioritizes environmental sustainability in water management, minimizes the use of chemical pesticides and fertilizers, reduces pests, and provides double benefits for farmers. This study aims to determine: the sustainability of mina padi from economic, social, and environmental aspects; analyze internal and external factors in mina padi; and design sustainability strategies for mina padi. The method used in this study is descriptive qualitative to describe the research results in greater depth. There are 13 informants in this study. The results of the study indicate that mina padi provides significant economic benefits, with an R/C Ratio of 1.24, meaning that every Rp 1 spent generates Rp 1.24 in revenue, making it worthwhile to pursue. Strategies that can be implemented for the sustainability of mina padi include: 1) increasing farmers' motivation to improve mina padi production through land intensification, such as the use of liquid organic fertilizer, adding natural feed, using high-quality seeds, and proper land preparation; 2) establishing partnerships with local restaurants and markets for sustainable absorption of harvests, 3) developing agrotourism with the support